2019
DOI: 10.3329/bccj.v7i1.40761
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of structure, organization and delivery of ICU care in Bangladesh

Abstract: Background : This study is a sub analysis of data submitted on behalf of Bangladesh to an international study (2013-2014) involving Asian ICUs and merits comparison with prior study done in Bangladesh in 2007 which had similar objective. Objective : To assess structure, organization and delivery of ICU care in ICUs of Bangladesh with attention to hospital organizational characteristics, ICU organizational characteristics, staffing etc. Method : Prospective cohort study involving ICUs of 51 hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The Saudi Critical Care Trials Group (SCCTG) has produced several highimpact papers [20][21][22] In addition, the reach of research led by the European Society of Intensive Care Medicine (ESICM) Trials Group, the Australian and New Zealand Intensive Care Society (ANZICS) Clinical Trials Group, the Canadian Critical Care Trials Group (CCCTG), and WFICC has extended to Asia [23][24][25][26][27][28][29][30]. Significantly, after an inaugural multinational effort on the Management Of Severe sepsis in Asia's Intensive Care unitS (MOSAICS) study [31], the ACCCT Group was formed in 2012 and has since conducted studies in 28 Asian countries and regions [9,11,[32][33][34][35][36], some of which have also published their own national data from these studies [37][38][39][40][41].…”
Section: Critical Care Researchmentioning
confidence: 99%
“…The Saudi Critical Care Trials Group (SCCTG) has produced several highimpact papers [20][21][22] In addition, the reach of research led by the European Society of Intensive Care Medicine (ESICM) Trials Group, the Australian and New Zealand Intensive Care Society (ANZICS) Clinical Trials Group, the Canadian Critical Care Trials Group (CCCTG), and WFICC has extended to Asia [23][24][25][26][27][28][29][30]. Significantly, after an inaugural multinational effort on the Management Of Severe sepsis in Asia's Intensive Care unitS (MOSAICS) study [31], the ACCCT Group was formed in 2012 and has since conducted studies in 28 Asian countries and regions [9,11,[32][33][34][35][36], some of which have also published their own national data from these studies [37][38][39][40][41].…”
Section: Critical Care Researchmentioning
confidence: 99%
“…We have observed that there are many districts with limited number of hospital beds also have no critical care facilities in those hospitals. It is also our observation from literature search that Bangladesh suffers from lack of sufficient trained doctors and nurses in critical care delivery 4 .…”
Section: Discussionmentioning
confidence: 86%
“…In 2013 -14 another study was done in Bangladesh involving 51 ICUs as apart of broader international study named as AISP study 3 . The Bangladesh part of the study was done with data from districts of Dhaka, Sylhet, Chattogram, Mymensingh and Savar and it involved 748 adult, pediatric and neonatal ICU beds 4 .…”
mentioning
confidence: 99%
“…10,11 However, the field of critical care struggles, as this sector lacks proper infrastructure, appropriate facilities and adequate qualified staff. 9,10,12,13 There is limited provision of formal teaching and training of critical care nursing staff, 9,12,13 especially in the realm of recognition of sudden patient deterioration. 9,13 Early Warning Scores, calculated from regularly observed bedside physiological parameters, have been proven to be a valuable tool to assess disease severity and prompt decision making.…”
Section: Introductionmentioning
confidence: 99%
“…9,10,12,13 There is limited provision of formal teaching and training of critical care nursing staff, 9,12,13 especially in the realm of recognition of sudden patient deterioration. 9,13 Early Warning Scores, calculated from regularly observed bedside physiological parameters, have been proven to be a valuable tool to assess disease severity and prompt decision making. 5 Such a scoring system does not require any costly investigation or invasive procedure, is easy to measure and document, and so is appropriate for resource limited settings.…”
Section: Introductionmentioning
confidence: 99%